The role of surfactant proteins SP-A and SP-D in viral infection: a focus on COVID-19 - O. S. Kharlamovа; K. Yu. Nikolaev; Yu. I. Ragino (Бюллетень сибирской медицины)
An immune response to invasion of viral pathogens is an integral part of maintaining the physiological functioning of the bronchopulmonary system and effective gas exchange. Collagen-containing C-type lectins (lung collectins) are some of the key proteins in the identification of viral particles. They have image-recognizing receptors that identify pathogen-associated molecular patterns, particularly viral glycoproteins. The surfactant proteins SP-A and SP-D, which are composed of trimerized units, belong to pulmonary collectins and oligomerize into higher-order structures. These proteins play an essential role in recognition and elimination of microbial pathogens (viruses, bacteria, fungi, parasites, nanoparticles, allergens) through a variety of mechanisms. Taking into account the burden of the novel coronavirus infection caused by the SARS-CoV-2 virus, it is important to consider the role of the surfactant proteins SP-A and SP-D in the pathogenesis of the immune response to viral invasion. Currently, there are data on the direct relationship between surfactant proteins and viruses belonging to the Coronaviridae family. The SP-A and SP-D proteins modulate inflammatory responses and cytokine synthesis, but prevent an excessive inflammatory response (cytokine storm). There is also an assumption that SARSCoV-2 directly suppresses and alters the production of surfactant proteins. Thus, the key pathogenetic role of the surfactant proteins SP-A and SP-D in the response to the viral pathogen SARS-CoV-2 is evident. Today, this is a promising area of translational medicine, which will contribute to a profound understanding of the pathogenesis of coronavirus infection for assessing the diagnostic and prognostic potentials of the surfactant proteins SP-A and SP-D in COVID-19. Additionally, it will help evaluate the therapeutic potential of recombinant fragments of human SP-A and SP-D.